2019
DOI: 10.1017/wet.2019.133
|View full text |Cite
|
Sign up to set email alerts
|

Droplet size impact on lactofen and acifluorfen efficacy for Palmer amaranth (Amaranthus palmeri) control

Abstract: Herbicide applications performed with pulse width modulation (PWM) sprayers to deliver specific spray droplet sizes could maintain product efficacy, minimize potential off-target movement, and increase flexibility in field operations. Given the continuous expansion of herbicide-resistant Palmer amaranth populations across the southern and midwestern United States, efficacious and cost-effective means of application are needed to maximize Palmer amaranth control. Experiments were conducted in two locations in M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Smaller droplets from non-air inclusion nozzles for POST herbicide applications at a constant volume have been reported to be more effective than larger droplets [24]. In contrast, many studies have reported no differences in weed control regarding droplet size when PPO-inhibiting herbicides [11,25,26,28,35] were applied to several weed species. Conflicting results found in the literature shows that herbicide efficacy is not solely dependent on droplet size.…”
Section: Discussionmentioning
confidence: 99%
“…Smaller droplets from non-air inclusion nozzles for POST herbicide applications at a constant volume have been reported to be more effective than larger droplets [24]. In contrast, many studies have reported no differences in weed control regarding droplet size when PPO-inhibiting herbicides [11,25,26,28,35] were applied to several weed species. Conflicting results found in the literature shows that herbicide efficacy is not solely dependent on droplet size.…”
Section: Discussionmentioning
confidence: 99%
“…Mayo et al (1995) reported a similar decline in Palmer amaranth control from 35% to 18% and 99% to 56% when acifluorfen and lactofen were applied at 14 and 28 d after soybean planting, respectively. Furthermore, Franca et al (2020) reported 52%-67% control of Palmer amaranth with lactofen or acifluorfen when plants were 15 cm tall at the time of application. Similarly, Gizotti de Moraes (2018) reported 40% and 54% control of Palmer amaranth with fomesafen and lactofen, respectively, when plants were at flowering stage (15-58 cm tall).…”
Section: Palmer Amaranth Controlmentioning
confidence: 99%
“…Spray droplet size can affect coverage of weeds and subsequent control. However, efficacy of herbicides is not always affected and can be variable depending upon a range of factors [7][8][9][10][11][12][13][14][15]. Efficacy of dicamba, glufosinate, and glyphosate was not affected by droplet size [8,11,12].…”
Section: Introductionmentioning
confidence: 99%